Virginity as a Choice: Expression of Gen Z about Sexual Agency in a Complex World - Effendi, Masitah; Rohma , Nur Faizatur; Prastiti, Jamalia Putri (Prodi Sosiologi Universitas Mataram, 2024)
In a complicated and evolving environment, this research delves deeply into the ways that men and women of Generation Z express their sexual agency about virginity. Social pressures, cultural conventions, and the fast advancement of technology are all present in today's environment. The authors discovered through extensive qualitative research techniques and explored the perspectives of Generation Z (Gen Z) individuals in Surabaya City, Indonesia, that Generation Z handles their decisions about virginity in very personal and distinctive ways, frequently questioning and opposing conventional standards and expectations. The research aims to understand how Gen Z navigates their sexual choices in a complex socio-cultural environment. This article also assesses the effects of Generation Z's choices about virginity on their mental, emotional, and physical well-being. The findings demonstrate that, depending on the person and social situation, these decisions can have important and diverse outcomes. However, the authors stress that further study is required to completely comprehend the ramifications of this decision. The study employs in-depth interviews and focus group discussions as primary data collection methods. Participants include Gen Z individuals aged between 18 and 24 years, residing in Surabaya city. All things considered, this article offers significant new perspectives on how Generation Z perceives and uses their sexual agency when they are virgins. By offering a greater understanding of how young people navigate and comprehend their sexuality in a complicated world. Keywords: Virginity; Gender; Generation Z; Sexual Right (Agency).